Respuesta :

Answer: B

[tex]x^{3} (4x-1) (4x-1)[/tex]

Step-by-step explanation:

Start with the given equation.

[tex]16^5 - 3x^3[/tex]

Start out by factoring the GCF.  x^3 is the GCF of both terms:

[tex]x^3 (16x^2 - 1)[/tex]

Use the different of squares method.:

[tex]a^2-b^2=(a+b)(a-b)[/tex]

[tex]a^2=16\\b^2=1[/tex]

Substituted the equations:

[tex]16^2-1^2=(a+b)(a-b)[/tex]

Factor:

 [tex]16x^2-1^2=(4x+1)(4x-1)[/tex]

Add GCF to the factor equation:

[tex]x^3(4x+1)(4x-1)[/tex]

ACCESS MORE